“First Catch Your Hare”: Some Difficulties with, and Contextual Factors in, Understanding (In)Appropriate Workplace Relationships - Steve Duck (Behavioral Sciences, 2022)
The article considers the contextual factors that lead to descriptions of workplace relationships as appropriate and inappropriate. It reviews viewpoint, context of activity, and the tension between social and personal relationships in environments based on task completion. If relationships are the sum of series of interactions, then interactions must be judged in context before compilation. The vantage point of viewers will complicate these assessments, as will the rhetorical purpose of the reporter.